Early Warning Systems for Financial Crises Applications to East Asia - Bank, Asian Development.; Bank, Asian Development. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2005)
Since the 1997 Asian financial crisis, East Asia has implemented a number of initiatives designed to strengthen monetary and financial cooperation, bolstering the region's resilience to economic and financial vulnerabilities. One such initiative is the ASEAN+3 Information Exchange and Policy Dialogue, which includes development of early warning systems (EWS) for financial crises. This book examines efforts to develop EWS models. Specifically, the book analyzes the current understanding of the causes of currency and banking crises, describes recent progress in developing and applying EWS models for currency and banking crises, reviews methodolgical issues, assesses the predictive power of EWS models and also highlights areas where further research is required to make these models more effective tools for policy analysis. The case studies apply both parametric and nonparametric approaches to EWS modleing using data from six East Asian countries.